Single nucleotide polymorphism in the COL11A2 gene associated with lowered heat pain sensitivity in knee osteoarthritis. Issue 1 (August 2017) - David Ho, Kwo Wei; Wallace, Margaret R; Sibille, Kimberly T; Bartley, Emily J; Cruz-Almeida, Yenisel; Glover, Toni L; King, Christopher D; Goodin, Burel R; Addison, Adriana; Edberg, Jeffrey C; Herbert, Matthew S; Bulls, Hailey W; et al.
Pain is one of the most prominent symptoms of osteoarthritis. However, there is often discordance between the pain experienced by individuals with osteoarthritis and the degree of articular pathology. This suggests that individual differences, including genetic variability in the central processing of nociceptive stimuli, may impact the presentation of osteoarthritis. Here, we show that the single nucleotide polymorphism rs16868943 in the collagen gene COL11A2 is significantly associated with lowered heat pain tolerance on the arm in participants with knee osteoarthritis ( P = 1.21 × 10 −6, P = 0.0053 after Bonferroni correction, beta = −3.42). A total of 161 knee osteoarthritis participants were included and evaluated for heat, punctate and pressure pain sensitivity of the affected knee and the ipsilateral arm. Each participant was genotyped for 4392 single nucleotide polymorphisms in genes implicated in pain perception, inflammation and mood and tested for association with pain sensitivity. The minor A allele of single nucleotide polymorphism rs16868943 was significantly associated with lower arm heat pain tolerance after correction for age, gender, race, and study site. This single nucleotide polymorphism was also nominally associated with other measures of heat pain sensitivity, including lowered knee heat pain tolerance ( P = 1.14 × 10 −5, P = 0.05 after Bonferroni correction), lowered arm heat pain threshold ( P = 0.0039, uncorrected) and lowered knee heat pain threshold ( P = 0.003, uncorrected). Addition of genotypes from 91 participants without knee pain produced a significant interaction between knee osteoarthritis status and the rs16868943 single nucleotide polymorphism in heat pain tolerance ( P = 1.71 × 10 −5 ), such that rs16868943 was not associated with heat pain tolerance in participants without knee pain ( P = 0.12, beta = 1.3). This is the first study to show genetic association with heat pain tolerance in individuals with osteoarthritis. The association is specific to participants who have already developed knee osteoarthritis, suggesting that the COL11A2 gene, which has previously been associated with familial osteoarthritis, may play a role in pain sensitization after the development of osteoarthritis.